2011
DOI: 10.1080/10503307.2011.565488
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists' spiritual, religious, atheist or agnostic identity and their practice of psychotherapy: A grounded theory study

Abstract: In this present grounded theory study, 16 experienced psychologists, who practiced from varied theoretical orientations and came from diverse religious/spiritual/nonreligious backgrounds, explored their personal religious/spiritual/nonreligious identity development journeys, their experiences with clients' religious/spiritual content in psychotherapy sessions, and how their identity may have influenced the way they interacted with religious/spiritual material during sessions. Results revealed that psychologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 25 publications
2
47
0
3
Order By: Relevance
“…Whilst research by Magaldi‐Dopman et al. () has elicited some similar categories, such as “challenges” that include “conflicts,” the findings discussed in this paper outline a comprehensive theoretical process that has not been elicited in any previous work.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Whilst research by Magaldi‐Dopman et al. () has elicited some similar categories, such as “challenges” that include “conflicts,” the findings discussed in this paper outline a comprehensive theoretical process that has not been elicited in any previous work.…”
Section: Discussionmentioning
confidence: 72%
“…() reported the influence of therapists’ theoretical orientation in their interactions with clients’ RS, whilst Baetz, Griffin, Bowen, and Marcoux () found that it was clinicians’ own RS beliefs, rather than practice guidelines, which “predicted inquiry into their patients’ spirituality” (p. 265). Findings from previous research implied the concept and impact of therapists’ perspective in their decisions (Baetz et al., ; Magaldi‐Dopman et al., ). However, the forming of perspectives and their numerous strands, as conceptualised in Florence's () research, contributes new knowledge to the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I used a qualitative grounded theory approach to gather and analyze the data (Foss & Waters, 2007;Glaser, 2011;Glaser & Strauss, 1967;Magaldi-Dopman, Park-Taylor, & Ponterotto, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Sweden is a multicultural country with different religious beliefs as well as non-religious identities or spiritualities. Magaldi-Dopman, Park-Taylor, and Ponterotto (2011) indicated by grounded theory that therapists' discussions of spiritual/religious material instigated in themselves anxiety and defensiveness, or energized them. The therapists were disturbed by their own strong emotions and felt that their own education had neglected spiritual/religious training.…”
Section: Psychiatric Nurses' Self-rated Competence and Clinical Envirmentioning
confidence: 99%